2013
DOI: 10.1038/srep01983
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing glass-forming ability via frustration of nano-clustering in alloys with a high solvent content

Abstract: The glass-forming ability (GFA) of alloys with a high-solvent content such as soft magnetic Fe-based and Al-based alloys is usually limited due to strong formation of the solvent-based solid solution phase. Herein, we report that the GFA of soft magnetic Fe-based alloys (with >70 at.% Fe to ensure large saturation magnetization) could be dramatically improved by doping with only 0.3 at.% Cu which has a positive enthalpy of mixing with Fe. It was found that an appropriate Cu addition could enhance the liquid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Since Fe 3 (B,P) contains three different elements and its structure is more complex, the crystallization process requires longer range atom rearrangements of constituent elements. As proved, the precipitation of α-Fe(Si) phase always undergoes competing process [31]. All of these will increase the thermal stability of molten alloy and the AFA.…”
Section: Constitutionmentioning
confidence: 92%
“…Since Fe 3 (B,P) contains three different elements and its structure is more complex, the crystallization process requires longer range atom rearrangements of constituent elements. As proved, the precipitation of α-Fe(Si) phase always undergoes competing process [31]. All of these will increase the thermal stability of molten alloy and the AFA.…”
Section: Constitutionmentioning
confidence: 92%
“…In another metallic glassformer, Li et al showed that tiny amounts of Cu (0.3%) could massively enhance the glass forming ability (suppress crystal nucleation) in Ferich (Fe>70 %) Fe-C-Si-B alloys [304]. This is believed to be due to the need to redistribute the Cu in order to enable the nucleation of Fe into clusters of α−Fe lattice that is the usual mechanism for crystallisation in these systems.…”
Section: Glassforming Ability In Metallic Systemsmentioning
confidence: 99%
“…Especially, after the discovery of Fe-based BMGs, they were considered to possess promising applications as magnetic, structural and surface coated materials59. However, they usually fracture catastrophically when deformed at room temperature, often undergoing only a few percent of plastic strain in compressions101112131415, which limits their widespread applications16.…”
mentioning
confidence: 99%